Ethnography Of Communication Analysis In Jane Eyre Movie (2011) - Pujianto, Riski, Dra. Malikatul Laila, M. Hum (2016)
Riski Pujianto. A320120114. ETHNOGRAPHY OF COMMUNICATION ANALYSIS IN JANE EYRE MOVIE (2011). Research Paper. School of Teacher Training and Education, Muhammadiyah University of Surakarta. August 2016. This research analyzes about ethnography of communication used in conversation based on topic variations in Jane Eyre movie (2011) uses SPEAKING theory by Dell Hymes. The aims of this research are (1) explaining the elements of ethnography of communication in Jane Eyre movie (2011) and (2) describing the inference in the use of the elements of ethnography of communication in Jane Eyre movie (2011). This research is analyzed using descriptive qualitative research. Based on the data analysis, the researcher finds: (1) Setting or scene is at St. John‟s house, Mrs. Reed house, Lowood School, Mr. Rochester‟s house, wood, park, backyard, and church. (2) Participants are Jane Eyre, St. John and his sisters, Mrs. Reed and John Reed, Mr. Brocklehurst, Helen, Mrs. Fairfax, Mr. Rochester, Adele, Sophie, Blanche Ingram, Lady Ingram, Richard Mason, Dr. Carter, Wood, Briggs, and Bertha Mason. (3) End are getting information, convincing, asking permission, introducing self, comanding, saying farewell, telling agreement and disagreement, telling experience, warning, expressing gratitude, giving argument, showing information, and asking apologize. (4) Act sequence has diffrent sequence based on the several of context and topic variations. (5) Key related to the tone used by the participants that are worries, anger, flat, fear, happy, admiration, regretful, jealous, scared, convincing, appeal, serious, resistance, and sad tone. (6) Instrumentalities are verbal and non-verbal communication. Non-verbal communication are found such as singing, crying, and piercing. (7) Norm are norm of tradition, reliance, social, decent and politeness. (8) Genre of communication in Jane Eyre movie (2011) is daily conversaton. The researcher finds that the use of language is influenced by topic variations and situations. From 28 data analyzed by the researcher, some data has completed the elements of ethnography of communication. But there are 7 data which has no completed the elements of ethnography of communication. The most missing elements are norm and ends. Keywords: ethnography of communication, speaking grid